2001
DOI: 10.1161/01.cir.103.3.442
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Hypertrophy Secondary to Pulmonary Hypertension Is Linked to Rat Chromosome 17

Abstract: Background-Fischer 344 (F344) rats are relatively resistant to hypoxia-induced right ventricular (RV) hypertrophy compared with the Wistar-Kyoto (WKY) strain. These 2 strains were used to examine the genetic basis for the differential response. Methods and Results-Male F 2 offspring from an F344ϫWKY intercross were exposed to hypoxia (10% O 2 ) for 3 weeks, and pulmonary artery pressure and cardiac chamber weights were measured. Genomic DNA was screened by use of polymorphic microsatellite markers across the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 37 publications
1
27
1
Order By: Relevance
“…All published heart weight/hypertrophy QTLs on chromosome 17 harbor a common interesting candidate gene, Drd1a (dopamine receptor 1a). [22][23][24][25][26][27][28][29][30][31][32][33] Overall, these results may demonstrate that rat chromosome 17 harbors major gene(s) involved in BP regulation as well as those involved in the regulation of major metabolic pathways and body homeostasis in LH rats.…”
Section: Bilusic Et Al Genetic Analysis In the Lyon Hypertensive Ratmentioning
confidence: 96%
See 1 more Smart Citation
“…All published heart weight/hypertrophy QTLs on chromosome 17 harbor a common interesting candidate gene, Drd1a (dopamine receptor 1a). [22][23][24][25][26][27][28][29][30][31][32][33] Overall, these results may demonstrate that rat chromosome 17 harbors major gene(s) involved in BP regulation as well as those involved in the regulation of major metabolic pathways and body homeostasis in LH rats.…”
Section: Bilusic Et Al Genetic Analysis In the Lyon Hypertensive Ratmentioning
confidence: 96%
“…Other studies have reported BP QTLs in the same region in 3 different F 2 intercrosses (Table 2). [22][23][24][25][26][27][28][29][30][31][32][33] We found that the angiotensin receptor 1a gene (Atr1a) is in this putative QTL region. All published heart weight/hypertrophy QTLs on chromosome 17 harbor a common interesting candidate gene, Drd1a (dopamine receptor 1a).…”
Section: Bilusic Et Al Genetic Analysis In the Lyon Hypertensive Ratmentioning
confidence: 99%
“…However, variation in the pulmonary vascular response to hypoxia is well recognized, both between and within species, 16,31,54,55 and in humans the magnitude of HPV can vary ≈5-fold among individuals. 16,55 Extreme responders are at highest risk of presenting acutely on arrival at altitude with high-altitude pulmonary edema (HAPE) or over weeks, months, and years with right heart failure secondary to severe pulmonary hypertension or excessive erythrocytosis.…”
Section: Clinical Presentations From Maladaptation To Hypoxia Variatimentioning
confidence: 99%
“…16,17 Numerous lines of clinical and experimental evidence have indicated that altered RyR-2 gene and function contribute to cardiac disorders, including catecholaminergic polymorphic ventricular tachycardia or arrhythmogenic right ventricular cardiomyopathy type 2, 15 cardiac hypertrophy, and dysfunction. 18,19 Furthermore, RyR-2 is hyperphosphorylated by protein kinase A (PKA) in HF, resulting in dissociation of FKBP12.6 from RyR-2 and Ca 2ϩ leaks from SR in diastole, which impair contractility. 16,17 Thus, alteration in RyR-2 is critically involved in abnormality of Ca 2ϩ handling and contractile dysfunction in HF.…”
mentioning
confidence: 99%